LEADERSHIP EFFECT AND DYNAMIC CAPABILITY ON THE SPEED OF DECISION MAKING IN HOSPITALS - Yulita, Maria Theresia; Nasution, Yasmine (PEOPLE: International Journal of Social Sciences, 2019)
This study analyzes the influence of strategy leadership style and dynamic capability on the speed of decision making with a focus on the object of research in the health industry known as a hospital. The background of the problems faced in this study is that hospitals face turbulent environmental changes and very tight competition that makes hospital management required to be able to make quick and appropriate decisions. Decision making, which is one of the main tasks of the leader, is the process of selecting several alternatives, where expertise is needed to take action, an efficient method that fits the situation. A leader in making decisions requires knowledge and accuracy of information from the problems faced quickly so that he can make accurate decisions, this is very useful to determine the solution of the choices taken. This study uses Hart's (1992) leadership theory which consists of: command, symbolic, rational, transactive, and generative. In addition to leadership factors, it is necessary to examine the influence of strategies where in the context of the dynamic environment a dynamic capability of a company will be used. Leaders must regularly make decisions about how to renew existing operational capabilities into new ones that are more in line with the changing environment, dynamic capabilities are an important challenge for management in their efforts to achieve sustainable competitive advantage. The research data was collected from 300 respondents who were midle management in hospitals. Data was analyzed using the help of SPSS 24 devices with regression techniques. The results of the study show that the company's dynamic capability is more give effect in the speed of decision making than leadership. Generative and rational leadership styles effect the speed of decision making. While dynamic capabilities moderate the effect of leadership on the speed of decision making.